A safe commutation strategy based on LRCD snubber circuit for five‐level active neutral point clamped inverter. Issue 3 (28th January 2021) - Ye, Weiwei; Nie, Ziling; Zhu, Junjie; Xu, Jie
Abstract: Spike voltage generated during the turn‐off transient is one of the key threats to IGBT. When the traditional RCD snubber is applied in the five‐level active neutral point clamped (5L‐ANPC) inverter to clamp the spike voltage, a transient large current caused by the charging of the snubber capacitor will increase power losses and current stresses of IGBTs. This study proposes a LRCD snubber for the 5L‐ANPC inverter. It can effectively suppress the spike voltages and the transient large currents of IGBTs, thus reducing the power loss. For the 5L‐ANPC inverter, the traditional commutation method also poses a threat to IGBTs. Near the zero‐crossing point of the output voltage, the traditional commutation method will cause the IGBTs that operate at the carrier frequency to withstand three times of the rated voltage. This study proposes a safe commutation strategy based on the LRCD snubber. When the output voltage passes through zero‐crossing point, the proposed commutation strategy uses four transition switching states to avoid the breakdown of IGBTs induced by overvoltage. It can ensure that all the IGBTs operate in the safe operating area (SOA). Experimental results are presented to verify the validity of the proposed method.